Enhancing Students’ Conceptual Reasoning on Pressure in Solids and Liquids through Team Games Tournament Cooperative Learning - Aulia Hana Faradiba; Ulinnuha Nur Faizah; Marzni Mohamed Mokhtar (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Persistent challenges in science education lie in transforming students from formula driven problem solvers into conceptually grounded scientific reasoners, particularly in abstract topics such as solid and liquid pressure. This study examined the effectiveness of the team games tournament (TGT) learning model in improving students’ conceptual reasoning on solid and liquid pressure topics. A quasi-experimental pre-test post-test control group design was employed, involving an experimental group taught using TGT and a control group receiving teacher centered instruction. Conceptual reasoning was assessed using a validated test addressing the relationship between force, surface area, and pressure, as well as fluid pressure concepts related to depth and container shape. The results showed a statistically significant difference in post-test conceptual reasoning scores between the experimental group (M = 74.72) and the control group (M = 59.12), with a mean difference of 17.66 points (p = 0.000 < 0.05). In addition, the experimental group demonstrated a significant pre-test to post-test improvement, as indicated by a moderate N-Gain score of 0.48 (47.78%), reflecting meaningful conceptual development. Further analysis revealed a very large instructional effect of the TGT model (Cohen’s d = 1.597), indicating strong practical effectiveness beyond statistical significance. These findings indicate that the TGT model effectively enhances students’ conceptual reasoning and reduces misconceptions in solid and liquid pressure learning, highlighting its potential as a powerful instructional approach in science education